2006
DOI: 10.1021/ef050352x
|View full text |Cite
|
Sign up to set email alerts
|

High Heat Sink Jet Fuels. Part 1. Development of Potential Oxidative and Pyrolytic Additives for JP-8

Abstract: It is anticipated that future jet fuels will be required to handle a thermal stress of approximately 900 °F (480 °C). Such an environment presents many challenges in providing fuels with the necessary thermal oxidative and pyrolytic stability. We report single-tube flow reactor data which suggests that addition of 100 ppm of dicyclohexylphenyl phosphine (DCP) to an air saturated JP-8, followed by stressing up to ∼675 °C, provides significant improvement in both thermal oxidative and pyrolytic stability. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The three-membered ring peroxides with the form R 3 PO 2 , where the R group represents alkyl or aryl substituents, were reported to act as intermediates in reactions of singlet oxygen with organic phosphines in solutions and in the gaseous phase at room temperature and higher temperatures [1][2][3][4][30][31][32]. There has been much recent interest to such 'exotic peroxides' -to quote from the title of a recent review by Sawwan and Greer [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-membered ring peroxides with the form R 3 PO 2 , where the R group represents alkyl or aryl substituents, were reported to act as intermediates in reactions of singlet oxygen with organic phosphines in solutions and in the gaseous phase at room temperature and higher temperatures [1][2][3][4][30][31][32]. There has been much recent interest to such 'exotic peroxides' -to quote from the title of a recent review by Sawwan and Greer [33].…”
Section: Resultsmentioning
confidence: 99%
“…Elucidation of the complicated mechanisms of these reactions is important for many practical applications. For example, substituted arylphosphines are being evaluated as potential additives for enhancing the stability of future jet fuels toward thermal oxidation [32,38]. Ph 3 P was shown to improve the thermal oxidative stability of jet fuel by at least 50% [39].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the thermal stability of jet fuel are separated into three regimes corresponding to differences in the bulk fuel temperatures. , The autoxidation regime starts at 150 °C and goes to 350 °C, the transition regime is in the range of 350–400 °C, and the pyrolytic regime is above 400 °C. Practical gas turbines usually operate in the lower range of the autoxidation regime, which has a much lower deposit rate than the pyrolytic regime .…”
Section: Methodsmentioning
confidence: 99%
“…Several other experimental rigs with single-tube heat-exchanger configurations have been reported in the literature, for example, the Shell Development Company Heat Transfer Test Rig, the NASA Glenn Research Center Heated Tube Facility, the Phoenix rig of the U.S. Air Force (USAF), the near-isothermal flowing test rig (NIFTR), the Australian Defence Science and Technology Organisation (DSTO) Thermal Stability Rig, , the flow reactor of the Pennsylvania State University (PSU) Energy Institute, , various designs from United Technology Research Center (UTRC), ,, and the single-tube heat-exchanger apparatus of the University of Toronto Institute for Aerospace Studies (UTIAS). ,, The test sections of these test rigs employ different methods for heating. For example, the Phoenix, NIFTR, and UTRC rigs embed the test section into a copper block and conductively heat it with an external electrical heater to achieve isothermal heating. ,, Test sections are also heated directly by flowing electrical current through them to achieve pyrolytic temperatures and constant heat flux in the Shell Heat Transfer Test Rig and others. A fluidized sand bath is used to heat the submerged test section in the DSTO rig, , whereas the PSU and UTIAS rigs use radiative heating of the test section by electrical tube furnaces. ,, …”
Section: Review Of Existing Test Rigsmentioning
confidence: 99%
“…The experiment was performed at 655 °C and 37 bar pressure with a feed flow rate of 2.9 mL/ min. It is reported that the coke formation reduced significantly (more than 13 times) in the presence of 300 ppm of diphenyl selenide in the fuel and for a test duration of 12 h. Sobkowiak et al 62 have investigated the influence of 65 studied the suitability of dicyclohexylphenylphosphine (DCP) on the coking performance of JP-8 fuel. The experiment was performed at 675 °C and 38 bar pressure using a flow reactor.…”
Section: Phenomena Of Coking During the Thermal Degradation Of Hydroc...mentioning
confidence: 99%